Effect of Covid-19 On Play and Recreation in Urban Slums of India: Perception of Adolescent Girls (Proceedings of the World Conference on Children and Youth, 2022)
As per Save the Children, WINGS Report (2018), only 20 percent of girls have access to playgrounds. Adolescent girls (10-18 years) from slums - face numerous challenges in realizing their right to access to safe, and inclusive spaces for play and recreation. COVID-19 has further exacerbated the already restricted access to play and recreation for girls. For many girls from informal settlements, playtime in school is the only opportunity for recreation, leisure, and meeting their friends. For this study, we adopted a mixed-methods approach; mainly a representative quantitative survey, focus group discussions, key-informant interviews. The survey uses the recall method to compare their situation between two timelines - (1) during lockdown (April to June 2020); (2) three months before the time of interview (November to January). In some questions, a third-time dimension was added to seek additional information on the situation before the pandemic. Data was collected from four states (Delhi, Maharashtra, Bihar, and Telangana). Two cities were selected from each state. Data has been collected from 1,092 girls and their mothers from the randomly selected slums. The survey was conducted during the first two weeks of February 2021. Nine out of ten mother respondents (88%) perceive play and recreation to be extremely important for girls. 50% girls reported that they missed the journey of going and coming back from school with their siblings and friends. Before the lockdown, streets were the preferred outdoor spaces for girls (40%). One in two girls (51%) reported that they were watching TV more as compared to pre-pandemic days. This was followed by household chores (two in five girls, 43%), use of mobile phones (two in five girls, 39%), and playing board games (one in three girls, 33%). There is an urgent need for multi-pronged efforts that should range from sensitization of city governments to investing in co-creating infrastructure and services - that enable girls to have safe access to play and recreation activities.
Keywords: lockdown; play and recreation; girls; adolescent; slums; city governments; COVID-19; India